Governing in a Polarized Era: Federalism and the Response of U.S. State and Federal Governments to the COVID-19 Pandemic. Issue 4 (14th August 2021) - Birkland, Thomas A; Taylor, Kristin; Crow, Deserai A; DeLeo, Rob
Abstract: How does the state of American federalism explain responses to COVID-19? State-by-state variations to the COVID-19 pandemic illustrate the political dynamics of "kaleidoscopic federalism, " under which there is no single prevailing principle of federalism. In the COVID-19 pandemic, features of kaleidoscopic federalism combined with shortcomings in the public health system under the Trump administration, leading to fragmented responses to the pandemic among the states. Federalism alone does not explain the shortcomings of the United States' response to the pandemic. Rather, the fragmented response was driven by state partisanship, which shaped state public health interventions and resulted in differences in public health outcomes. This has sobering implications for American federalism because state-level partisan differences yield different and unequal responses to the pandemic.